Our Constitution a conversation. - O'Connor, Sandra Day, 1930-2023.; Breyer, Stephen G., 1938-; Annenberg Foundation Trust at Sunnylands; Annenberg Public Policy Center ([Philadelphia, Pa.?] : Annenberg Foundation Trust at Sunnylands, 2005)
United States Supreme Court Justices Sandra Day O'Connor and Stephen Breyer talk about the Constitution with high school students and discuss why we have and need a constitution, what federalism is, how implicit and explicit rights are defined and how separation of powers ensures that no one branch of government obtains too much power.
Introduction -- Teaching the Constitution -- Why have a constitution? -- Helping to solve problems -- The power of precedent -- Moral values/Decision-making -- Separation of powers -- Relevance today -- Federalism -- Individual liberty vs. security -- Most influential cases -- Court decision making -- Conclusion.
Prepared for Constitution Day 2005.
"Created by The Annenberg Foundation Trust at Sunnylands in partnership with the Annenberg Public Policy Center of the University of Pennsylvania."
DVD.
Keywords: United States; Constitutional law -- United States; Federal government -- United States; United States -- Politics and government